Astuti, G., Roma-Marzio, F. & Peruzzi, L. (2015) The genus Picris (Asteraceae) in southern Italy: contribution to its systematic knowledge. Phytotaxa 207 (1): 106–114. - Astuti, Giovanni; Roma-Marzio, Francesco; Peruzzi, Lorenzo (Phytotaxa, 2015)
.